Calcifying Epithelial Odontogenic Cyst Associated with Complex Odontome of Maxilla - Rastogi, Vikalp (Springer-Verlag, 2011)
The term calcifying odontogenic cyst was first introduced by Gorlin in 1962 (Eshghyar et al., Acta Med Iran 44(1):59–62, 2006). The lesion is unusual in that it has some features of a cyst but also has many characteristics of a solid neoplasm (Cysts and tumors of odontogenic origin: textbook of oral pathology, 2006). It is classified into two types—Type I-the cystic variant, Type II-solid tumor variant. This case report present Type I B-odontome producing intraosseous calcifying odontogenic cyst and Type I C-with ameloblastomatous proliferation in a 19 years old male patient in the right maxillary quadrant. The lesion involved an unerupted permanent maxillary central incisor, which was displaced to the infraorbital ridge of right side and the radiograph revealed a calcified mass in the periapical region of right incisor that was later recognized histopathologically as complex composite odontoma. The lesion was removed surgically. This case report emphasizes on the presence of this Type I B and C lesion and the need to keep them in follow up.